Effect of Fushengong Decoction on PTEN/PI3K/AKT/NF-κB Pathway in Rats With Chronic Renal Failure via Dual-Dimension Network Pharmacology Strategy - Luo, Hongyu; Wang, Munan; Xu, Ke; Peng, Qiyao; Zou, Bo; Yin, Shi; Yu, Chao; Ren, Lingyan; Li, Ping; Tang, Li; Peng, Yongbo; Huang, Xuekuan (Frontiers in Pharmacology, 2022)
The treatment of chronic renal failure (CRF) with traditional Chinese medicine has attracted much attention, but its mechanism is not clear. Network pharmacology is an effective strategy for exploring the interaction mechanisms between Chinese herbs and diseases, however, it still needs to be validated in cell and/or animal experiments due to its virtual screening characteristics. Herein, the anti-CRF mechanism of the Fushengong decoction (FSGD) was investigated using a dual-dimension network pharmacological strategy combined with in vivo experiment. Methods: The Traditional Chinese Medicine Systems Pharmacology (TCMSP) database (https://tcmspw.com) and UHPLC-MS/MS technology were used to identify the effective compounds of FSGD in theory and practice, such as quercetin, formononetin, and pachymic acid. The putative targets of FSGD and CRF were obtained from the Swisstarget prediction platform and the Genecards database, respectively. The common target pathways between FSGD and CRF were got from the dual-dimension network pharmacology analysis, which integrated the cross-common targets from the TCMSP components-Swisstarget-Genecards-Venn platform analysis in theory, and the UHPLC-MS/MS identified effective ingredients-Swisstarget screening, such as TNF and PI3K/AKT. Furthermore, system molecular determinations were used to prove the dual-dimension network pharmacology study through CRF rat models, which were constructed using adenine and treated with FSGD for four weeks. Results: A total of 121 and 9 effective compounds were obtained from the TCMSP database and UHPLC-MS/MS, respectively. After dual-dimension network pharmacology analysis, the possible mechanism of PTEN/PI3K/AKT/NF-κB pathway was found for FSGD in CRF. In vivo experiments indicated that FSGD can play a role in protecting renal function and reducing fibrosis by regulating the PTEN/PI3K/AKT/NF-κB pathway. These findings provide a reference for FSGD in CRF. Conclusion: Based on the theoretical and practical dual-dimension network pharmacology analysis for FSGD in CRF, the possible molecular mechanism of PTEN/PI3K/AKT/NF-κB was successfully predicted, and these results were verified by in vivo experiments. In this study, the dual-dimension network pharmacology was used to interpret the key signal pathway for FSGD in CRF, which also proved to be a smart strategy for the study of effective substances and pharmacology in FSGD.